ANALISIS PENGARUH BESAR GESEKAN TERHADAP TEGANGAN THERMAL PADA SEPATU REM MOBIL KETEBALAN 5 MMMENGGUNAKAN PERANGKAT LUNAK MSC.NASTRAN V.9 - Lubis, Sudirman (Jurusan Teknik Mesin, Fakultas Teknologi Industri, Institut Teknologi Medan (ITM), 2019)
Braking failure better known as brake failure is caused by many factors, but one factor is due to excess heat that occurs in optimal braking conditions when the vehicle is driving at high speed and sufficient distance. The purpose of this research is to obtain the result of thermal stress simulation during braking, in special area of brake shoe with 8 mm thickness. However, it is unlikely that brake shoe is analyzed manually because brake shoes have many vertices, even up to thousands of vertices. So we need the software support finite element finishing method of MSC. NASTRAN V9 to simulate the distribution of temperature distribution on brake shoe for easy analysis. Thermal stresses that occur in the brake shoe with a thickness of 5 mm in this study that the model brake shoe model 2 has a maximum thermal voltage of 5.7326 Mpa and 0.2329 Mpa Minimum lower than the brake shoes model 1 thermal 5.8155 Mpa maximum voltage and 1.1629 Mpa Minimum. With a maximum test difference of 1.42% and a minimum of 79.97%.